Measuring factors affecting customer loyalty on Islamic banking deposit in Malaysia - Warsame, Ahmed Essa (2015)
The growth of Islamic banking assets in Malaysia shows a remarkable growth for the recent years. The total assets of Islamic banking have risen RM 469.5 billion with an average 24.2% growth per year. In spite of this phenomenal growth, Islamic banking only gain 20% of banking industry market share. In order to increase its market share, the Islamic banks must satisfy their customers. The purpose of the study is to determine factors that affecting customer loyalty on Islamic banking deposit. This study was conducted primary data collected through a questionnaire and email survey from Bank Islam customers in Universiti Utara Malaysia (UUM). The study w as carried out by taking a sample of 2 17 respondents only 1 18 responses were further analysed by using SPSS software. The result revealed that customer satisfaction, perceived value, and trust have significant influence on customer loyalty on Islamic banking deposit. This study empirically contributes to the practical implication of Islamic banking managers in order to understand customer's anticipations. Managers of Islamic banks have to place prime the importance of customers by building these factors to enhance their customer's loyalty. Moreover, the study presented valuable information about the expansion and development of Islamic banks, as well as the market behaviour of Islamic banking customers in Malaysia. In order to increase Islamic banking market share in this modern customer-centric competitive arena, the bank has to satisfy and show value to their customers. Nevertheless, Islamic banking managers can formulate the strategies to retain their customers and attract new customers